A secure reversible chaining watermark scheme with hidden group delimiter for WSNs. (3rd September 2019) - Wang, Baowei; Ding, Qun; Gu, Xiaodu
Chaining watermarks are considered to be one of the most practical methods for verifying data integrity in wireless sensor networks. But the synchronisation points (SPs) or the group delimiters (GDs), which are indispensable to keep the sender and receivers synchronised, have been the biggest bottlenecks of existing methods: 1) If the SPs are tampered, the false negative rate will be up to 50% and make the authentication meaningless; 2) The additional GDs are easily detected by adversaries. We propose a more secure reversible chaining watermark scheme, called RWC, to authenticate the data integrity in WSNs. RWC has the following characteristics: 1) Fragile watermarks are embedded in a dynamic grouping chaining way to verify data integrity; 2) Hidden group delimiters are designed to synchronise the sending and receiving sides in case of the SPs are tampered; 3) A difference expansion-based reversible watermark algorithm can achieve lossless authentication. The experimental results show that RWC can authenticate the sensory data with free distortion and significantly improve the ability to detect various attacks.